The reflection of the social nature of man in Dostoyevsky's work - Serdiuchenko, V. (Literatūra, 1969)
The purpose of the article is to make clear why the theme of individualism is so popular in Dostoyevsky's works. The article says that Dostoyevsky pays so much attention to the selfish, criminal origin in a human being not to express his nihilism or to pursue any artistic purposes, on the contrary it serves to deny this origin; just for this purpose. Dostoyevsky develops the individualistic idea up to such ontological heights in order to deny it with the same ontological convince. Finally Dostoyevsky states that human "I" is absolutely collective, inseparable from the fate of the whole mankind. Thus, Dostoyevsky's anthropological views do not contradict his materialistic definition of man as a product of social relations. Instead we see that Dostoyevsky is one of the most furious enemies of any anthropological conceptions of materialism and socialism. The reason of the above paradox lies, to the author's mind, in the mere fact that Dostoyevsky does not originate the human collectivism from the collectivism of his material existence, replacing sociality by "Sobornost" – an idealistic, religious term, expressing some aprioric quality of a man aside from history and social practice.
Keywords: -